KARAKTER DOODLE DALAM KARYA KERAJINAN KERAMIK - Delsy Ifdahalul Afni; Jupriani Jupriani (Universitas Negeri Padang, 2021)
The purpose of creating works is to create ceramic craft products that have aesthetic value or beauty as well as a certain function. Of the various materials or craft-making techniques, ceramics are an interesting medium, because the processing can be done by hand or with simple tools. Crafts also use ornaments. Ornaments on crafts can add uniqueness and aesthetic value. The ornament used in this work is the Doodle character, where Doodle itself has the meaning of spontaneous scribbles and is also a popular modern art work from all circles almost all over the world.The method of creating works of art uses five stages, namely preparation for elaboration, synthesis, concept realization, and completion. Hold an exhibition of ceramic works, in the creation of works, using clay materials with printing techniques, pinching (massage) and using original colors after burning. Eleven iii works are made in accordance with the form of works, namely in the form of animals and cartoons with doodle characters as ornaments. With the following title: fish with doodle ornaments, one type of repeating flower motif. Turtles with doodle ornaments are one type of repeating floral motif. Turtle with floral doodle ornament with floral pattern. Frog with repeating floral doodle ornament floral motif. A whalewith a doodle ornament and several floral motifs combined. Larvae with doodle ornaments and several repeating flower motifs. Owl child with a doodle ornament, one type of separate flower motif. Owl with doodle ornaments and several kinds of mixed motifs. Pig with doodle ornaments and some floral motifs. Rabbit with doodle ornament and one repeating flower motif. Angry bird with doodle ornaments and one type of repeating flower motif.Key words: ceramics, ornament, doodle.